Bentuk Penyajian Dan Nilai Filosofi Tari Muwang Sangkal Sumenep Untuk Anak Kelas VI Di sekolah Dasar - Muhammad Misbahudholam AR; Framz Hardiansyah; Sama’ Sama’ (Edumaspul: Jurnal Pendidikan, 2021)
The philosophy and values ​​of the Muwang Sumenep Dance were studied in this study for the sixth-grade students of SDN Pandian V Sumenep. In this study, Grade VI students of SDN Pandian V Sumenep will learn about the Dance Philosophy of Muwang Sangkal Sumenep. It uses a descriptive method that focuses on describing what is described. Observational structured interviews and documentation approaches were taken to collect data for this study. According to the findings, dance classes are held twice a week at SDN Pandian V Sumenep. For students of SDN Pandian V Sumenep, dance classes are held to hone and develop their talents. In addition, they can see how the philosophy is presented and how important it is overall. To perform the Muwang Sangkal dance, children only need to learn the sequence of movements. Meanwhile, children can learn in detail and clearly about the philosophical values ​​of Muwang Sangkal dance, such as the requirements for a Muwang Sangkal dancer to be pure and not menstruating and to be humble and not arrogant. For elementary school students, Muwang Sangkal dance theory is the same as Muwang Sangkal dance theory in general. Makeup and fashion are just two of the many differences between men and women. The Sumenep Muwang Sangkal dance has been recognized as a symbol of the Sumenep Regency by the Sumenep community and has become a source of pride for the Sumenep people.